Hubungan Hygiene Sanitasi Pedagang Air Tahu Terhadap Angka Kuman Di Kecamatan Pontianak Selatan - Putri, Dwi Sabrina Aisya; Saepudin, Malik; Sunarsieh, Sunarsieh; Martini, Martini (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2024)
There are still many tofu water vendors in South Pontianak City who carry out the process of selling and packaging unhygienic tofu water, such as using rinse water in washing tubs that do not replace water and there are still many traders who place tofu water in open containers which allows for bacterial contamination due to exposure to dust from the streets and the dirty surrounding environment. This can increase the high number of germs on food equipment and contamination of tofu water. Analyzing the relationship between sanitation hygiene (traders, food equipment sanitation, and environmental sanitation) with the number of germs in tofu water in South Pontianak in 2023. The research design used in this research is observational analytic, that is, research that aims to explain the relationship between the independent variable and the dependent variable. From the results of bivariate statistical tests with the chi-square test at a confidence level of 95% (a 0.05) it was obtained that p > α (0.05), so that Ha was rejected, which means there is no significant relationship between Personal Hygiene, sanitation of traders, sanitation of equipment, and environmental sanitation with the number of germs in tofu water sold in South Pontianak District. Based on the results of research conducted, it is known that low germ numbers and high germ numbers have the same ratio with each percentage being 50%. There is no significant relationship between Personal Hygiene, sanitation of traders, sanitation of equipment, and environmental sanitation with the number of germs in tofu water sold in South Pontianak District, p value > α (0.05). It is necessary to increase traders' knowledge about food sanitation by participating in education and reading applicable food sanitation regulations. Recommendations that can be given to future researchers are to examine this problem further from other factors, such as carrying out laboratory tests on the clean water used to see the number of germs contained in the clean water and examining the hailstone raw materials used.